Shifting gears higher - digital slides in graduate education - 4 years experience at Semmelweis University - Molnár Béla; Cserneky Mária; Gerely László; Fónyad László; Matolcsy András (BMC, 2010)
Abstract Background The spreading of whole slide imaging or digital slide systems in pathology as an innovative technique seems to be unstoppable. Successful introduction of digital slides in education has played a crucial role to reach this level of acceptance. Practically speaking there is no university institute where digital materials are not built into pathology education. At the 1st. Department of Pathology and Experimental Cancer Research, Semmelweis University optical microscopes have been replaced and for four years only digital slides have been used in education. The aim of this paper is to summarize our experiences gathered with the installation of a fully digitized histology lab for graduate education. Methods We have installed a digital histology lab with 40 PCs, two slide servers - one for internal use and one with external internet access. We have digitized hundreds of slides and after 4 years we use a set of 126 slides during the pathology course. A Student satisfaction questionnaire and a Tutor satisfaction questionnaire have been designed, both to be completed voluntarily to have feed back from the users. The page load statistics of the external slide server were evaluated. Results The digital histology lab served ~900 students and ~1600 hours of histology practice. The questionnaires revealed high satisfaction with digital slides. The results also emphasize the importance of the tutors' attitude towards digital microscopy as a factor influencing the students' satisfaction. The constantly growing number of page downloads from the external server confirms this satisfaction and the acceptance of digital slides. Conclusions We are confident, and have showed as well, that digital slides have got numerous advantages over optical slides and are more suitable in education.